Visual attention in change blindness for objects and shadows. (September 2022) - Hermens, Frouke; Zdravković, Sunčica
Studies have found that observers pay less attention to cast shadows in images than to better illuminated regions. In line with such observations, a recent study has suggested stronger change blindness for shadows than for objects (Ehinger et al., 2016). We here examine the role of (overt) visual attention in these findings by recording participants' eye movements. Participants first viewed all original images (without changes). They then performed a change detection task on a subset of the images with changes in objects or shadows. During both tasks, their eye movements were recorded. In line with the original study, objects (subject to change in the change detection task) were fixated more often than shadows. In contrast to the previous study, better change detection was found for shadows than for objects. The improved change detection for shadows may be explained by the balancing of trials with object and shadow changes in the present study. Eye movements during change detection indicated that participants searched the bottom half of the images. Shadows were more often present in this region, which may explain why they were easier to find.